THE EFFECT OF SERVICE QUALITY, BRAND IMAGE AND PRICE PERCEPTION ON SALES VOLUME OF VIVO BRAND SMARTPHONES (survey on consumers of PT. Finansia Multi Finance, Bangkinang Branch) - Setiawan, Arisman; Arman, Arman; Yusril, Muhammad (Jurnal Riset Manajemen Indonesia, 2021)
This study aims to determine the effect of service quality, brand image and price perception on sales volume of Vivo brand smartphones (survey on consumers of PT. Finansia Multi Finance, Bangkinang Branch). This research was conducted by distributing questionnaires to 91 consumers who bought the Vivo brand smartphones. The type of data used consists of primary data and secondary data. These data were collected using a questionnaire and research files. From the results of the validity test, all items of the statements submitted to the respondents were declared valid with a value of rcount greater than the value of rtable (0.206). Reliability test results also indicate that each item has a good level of reliability with Cronbach's alpha value above 0.6. From the results of the study concluded that the independent variables partially affect the sales volume at PT. Finansia Multi Finance Bangkinang Branch. The analytical tool used to measure the effect of the independent variable on the dependent variable is multiple linear regression. The correlation coefficient (R) is 0.668 with the coefficient of determination (R2) of 42.60%. The results of this study indicate that the variables of service quality, brand image and price perception affect the sales volume at PT. Finansia Multi Finance Bangkinang Branch.